THE EFFICACY OF WAQF LAND DISPUTE SETTLEMENT THROUGH NON-LITIGATION MEDIATION - Islamiyati Islamiyati; Rofah Setyowati; Dewi Hendrawati; Aisyah Ayu Musyawah; Ahmad Rofiq (Magister Kenotariatan Universitas Pasundan, 2022)
In Indonesia, rapid expansion of waqf land had great impact on the waqf dispute that had to be resolved. Waqf dispute might be settled through consensus and mediation. In fact, it showed that waqf dispute settlement through mediation was ineffective because it was not based on appropriate mediation principle. This study would find out and analyze the problems in waqf dispute settlement through mediation based on the perspective of the efficacy of law theory in Central Java. Sociolegal research with empirical juridical approach was used as the research method, primary and secondary data were the data needed, while the analysis was done qualitatively. The result of the study showed that, based on efficacy of law theory, waqf dispute settlement through mediation outside the court had been ineffective, because it had some problems in; legislation formal juridical, law enforcement institutional, media or facility on law enforcement human resources, society compliance on the law, and legal culture customary law in society. The efficacy of waqf dispute settlement through mediation outside the court was settled through an innovation on the field of regulation, institution, human reources, and legal culture, in order to get fair and thorough settlement on the waqf dispute in society.